Dynamic Roles and Expanding Diversity of Adipose Tissue Macrophages in Obesity - Shindy Soedono; Vivi Julietta; Hadia Nawaz; Kae Won Cho (Journal of Obesity & Metabolic Syndrome, 2024)
Adipose tissue macrophages (ATMs) are key regulators of adipose tissue (AT) inflammation and insulin resistance in obesity, and the traditional M1/M2 characterization of ATMs is inadequate for capturing their diversity in obese conditions. Single-cell transcriptomic profiling has revealed heterogeneity among ATMs that goes beyond the old paradigm and identified new subsets with unique functions. Furthermore, explorations of their developmental origins suggest that multiple differentiation pathways contribute to ATM variety. These advances raise concerns about how to define ATM functions, how they are regulated, and how they orchestrate changes in AT. This review provides an overview of the current understanding of ATMs and their updated categorization in both mice and humans during obesity. Additionally, diverse ATM functions and contributions in the context of obesity are discussed. Finally, potential strategies for targeting ATM functions as therapeutic interventions for obesity-induced metabolic diseases are addressed.